The Contribution of the Silk Road to Etnocultural Development in the History of International Relations (International relations and international law Journal, 2025)
The relevance of the study is due to the importance of examining the historical significance of the Great Silk Road (GSR) in the context of international relations and ethno-cultural development. The Great Silk Road played a key role in establishing trade, diplomatic, and cultural ties between the East and the West. In the modern era of globalization, studying the historical experience of civilizational interaction through the GSR helps to develop strategies for economic and cultural cooperation between the countries of Eurasia. Moreover, an in-depth analysis of its historical role contributes to expanding scientific knowledge about the mechanisms of cultural diffusion, interethnic interaction, and the formation of transnational networks, which is particularly important for contemporary historical science and the practice of international relations.The aim of the study is to analyze the contribution of the Great Silk Road to the ethno-cultural development of international relations, to identify its impact on the formation of inter-civilizational contacts and the exchange of knowledge, technologies, and cultural values. The research is also aimed at studying the political and economic context of the GSR's functioning and its influence on the development of the states within its sphere of influence.The methodological basis of the study includes historical-comparative analysis, a systematic approach, methods of historical retrospection, and comparative studies. The use of these methods allows for a comprehensive examination of the interconnection of trade, political, and cultural processes that took place along the Great Silk Road. A comprehensive interdisciplinary approach makes it possible to take into account the economic, social, and cultural aspects of the development of ancient trade routes, making the study more complete and objective.The practical significance of the study lies in the possibility of applying the obtained results in the development of modern strategies for economic and cultural cooperation between the countries located along the historical route of the GSR. The analysis of historical experience contributes to a deeper understanding of the mechanisms of international interaction, which is particularly relevant in the context of initiatives to revive the Silk Road, such as China's "Belt and Road" project. Furthermore, the study materials can be used for educational purposes, particularly in the preparation of academic courses on the history of international relations, cultural studies, and Oriental studies. The research may also be useful for diplomats, experts in international trade and logistics, as well as for government agencies involved in the development of international cooperation.Thus, the study of the Great Silk Road as a factor in ethno-cultural development allows for the identification of historical patterns in the formation of international contacts and also contributes to the development of modern logistics and trade diplomacy in the Eurasian region.Key words: Great Silk Road, history of international relations, Central Asia, East-West dialogue, Transcontinental project, international trade, multicultural model